Clinical Response to Xultophy Possibly Varies from Each Different Metabolic Function - Bando, Hiroshi; Sakamoto, Kazuki; Ogawa, Tomoya; Kondo, Naoki; Hatakeyama, Shigeki; Kobayashi, Toshiharu; Iwatsuki, Noboru (Edelweiss Applied Science and Technology, 2021)
Two patients with Type 2 Diabetes Mellitus (T2DM) were treated with Xultophy. Xultophy consists of degludec and liraglutide (IDegLira). It is the combination of long-acting insulin and Glucagon like Peptide-1 Receptor Agonist (GLP-1RA) and is characteristic for effective agent for improving glucose variability for patients with T2DM. However, clinical responses are not always satisfactory due to different complication and background of each patient. We have experienced two impressive T2DM cases. Case 1 was 59-year-old male with hypertension for 20 years and T2DM for 3 years. He was treated on Novolin 30R 30/21 units twice a day, and after that Xultophy 32 doses brought him successful glucose profile. Case 2 was 78-year-old male with hypertension, bronchial asthma, hyperuricemia, and others with heavy alcohol drinking for 50 years. He was formerly treated by Insulin detemir, Liraglutide, exenatide and Degludec/NovoRapid, but has been recently unstable in glucose control. Xultophy up to 40 doses could not successfully improve glucose variability. One of the less responsiveness to Xultophy would be due to impaired liver function. Clinical progress of both cases associated with several perspectives from various points of view are discussed in this article.